2013
DOI: 10.1007/s10436-013-0236-3
|View full text |Cite
|
Sign up to set email alerts
|

Implied cost of capital investment strategies: evidence from international stock markets

Abstract: Investors can generate excess returns by implementing trading strategies based on publicly available equity analyst forecasts. This paper captures the information provided by analysts by the implied cost of capital (ICC), the internal rate of return that equates a firm's share price to the present value of analysts' earnings forecasts. We find that U.S. stocks with a high ICC outperform low ICC stocks on average by 6.0% per year. This spread is significant when controlling the investment returns for their risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The ICC can be defined as the internal rate of return that equates share prices to discounted analysts’ cash flow forecasts. Although several assumptions have to be applied when using this method, it is more popular for country‐level analysis (Esterer & Schröder, ).…”
Section: Empirical Strategymentioning
confidence: 99%
“…The ICC can be defined as the internal rate of return that equates share prices to discounted analysts’ cash flow forecasts. Although several assumptions have to be applied when using this method, it is more popular for country‐level analysis (Esterer & Schröder, ).…”
Section: Empirical Strategymentioning
confidence: 99%
“…Despite the value relevance of analysts’ forecasts, prior research has also shown that stock price reactions to earnings announcements are stronger than the response to analysts’ forecast revisions (Bartov et al , 2002; Esterer and Schröder, 2014). Consistent with the notion that earnings figures are important to investors (Ammer and Ahmad-Zaluki, 2017; Hlel et al , 2019), recent research shows that firms actively manage their earnings (or analysts’ expectations) to MBE forecast consensus (Bartov et al , 2002; Kim and Song, 2015; Masumoto, 2002; Zhang et al , 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Lee et al (2009) employs the ICC to test asset pricing models, while Pástor et al (2008) and Chava and Purnanandam (2010) analyze the risk-return trade-off of shares. Li et al (2013) and Esterer and Schröder (2014) use the ICC to predict stock returns.…”
Section: Introductionmentioning
confidence: 99%